2022
DOI: 10.48550/arxiv.2201.12366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cosmological Fast Optical Transients with the Zwicky Transient Facility: A Search for Dirty Fireballs

Abstract: Dirty fireballs are a hypothesized class of relativistic massive-star explosions with an initial Lorentz factor Γ init below the Γ init ∼ 100 required to produce a long-duration gamma-ray burst (LGRB), but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 143 publications
(211 reference statements)
0
5
0
Order By: Relevance
“…The best-fit power-law index is Γ X = 1.53 ± 0.03, and host galaxy absorption is N H = 1.09 +0. including superluminous SNe (SLSN), Type Ia SNe (SN Ia), core-collapse SNe [66][67][68] , luminous fast blue optical transients(LFBOTs) 41, 42, 45-47, 68, 69 , GRB afterglows 69,70…”
Section: Neutron Star Interior Composition Explorermentioning
confidence: 99%
“…The best-fit power-law index is Γ X = 1.53 ± 0.03, and host galaxy absorption is N H = 1.09 +0. including superluminous SNe (SLSN), Type Ia SNe (SN Ia), core-collapse SNe [66][67][68] , luminous fast blue optical transients(LFBOTs) 41, 42, 45-47, 68, 69 , GRB afterglows 69,70…”
Section: Neutron Star Interior Composition Explorermentioning
confidence: 99%
“…Kool et al (2021) discovered the afterglow about 38 minutes after the initial burst. They also reported a non-detection of the same object in serendipitous observations of the field about 1.9 hours prior to their first detection (see Andreoni et al (2021) and Ho et al (2022) for discovery details). Follow-up observations obtained by various groups (see for instance Table A2) revealed that the source was indeed the fading afterglow of GRB 210204A and measured the source redshift.…”
Section: X-ray Afterglowmentioning
confidence: 93%
“…Localizations for about a few dozen of the brightest GRBs per year are published in GCN circulars 8 . Recently, rapid IPN localizations have facilitated significant discoveries in the GRB field, e.g., the localization of the short GRB 170817A, the counterpart of the gravitational wave event GW170817 from a binary neutron star merger [22], the detection of the extragalactic magnetar giant flare in NGC 253 [111], the discovery and confirmation of the shortest GRB from a collapsar [112], and the association of a number of GRBs with fast optical transients [113].…”
Section: The Interplanetary Networkmentioning
confidence: 99%